Засоби фінансової стратегії підприємства - Аметова, Е.Е.; Артюхова, І.В. (Культура народов Причерноморья, 2013)
У статті досліджується сутність стратегічного управління фінансами підприємства як найважливішої складової забезпечення конкурентних переваг в процесі реалізації стратегічних цілей його економічного розвитку та визначені засоби поліпшення фінансових показників підприємства. У результаті дослідження обгрунтовується ефективність застосування фінансової стратегії на підприємстві. Відзначено, що її перевага полягає в ефективному формуванні та використанні фінансових ресурсів. У процесі дослідження виявлено найбільш ефективні напрями інвестування, що засноване на оперативному вивченні взаємозв'язку і залежності між обсягом виробництва, витратою і виручкою. Таким чином, на підставі одержуваної інформації можна приймати ефективні управлінські рішення. Ключові слова: фінансова стратегія, прогнозування, планування, фінансові ресурси, баланс підприємства В статье исследуется сущность стратегического управления финансами предприятия как важнейшей составляющей обеспечения конкурентных преимуществ в процессе реализации стратегических целей, его экономического развития и определены средства улучшения финансовых показателей предприятия. В результате исследования обосновывается эффективность применения финансовой стратегии на предприятии. Отмечено, что ее преимущество заключается в эффективном формировании и использовании финансовых ресурсов. В процессе исследования выявлены наиболее эффективные направления инвестирования, что основано на оперативном изучении взаимосвязи и зависимости между объемом производства, затратой и выручкой. Таким образом, на основании получаемой информации можно принимать эффективные управленческие решения. Ключевые слова: финансовая стратегия, прогнозирование, планирование, финансовые ресурсы, баланс предприятия The article examines the nature of the strategic financial management of the enterprise as an essential component of competitive advantage in the implementation of the strategic objectives of its economic development, and by means of improving the financial performance of the company. The study substantiates the effectiveness of the financial strategy of the company. Noted that its strength lies in the effective formulation and use of financial resources. The study found the most effective areas of investment, which is based on the operational study of the relationship and the relationship between the volume of production, costs and revenues. Thus, on the basis of information received can make effective management decisions. The success of the financial strategy of the company is guaranteed when the strategic financial objectives correspond to the real economic and financial capacity. In article the proposed means of improving financial indicators. The first proposed measure in the financial strategy for the company is to provide discounts to customers. Terms of payment can be selected so as to make an early payment more attractive to buyers. Increased marketing activities of the company will result in increased sales and, consequently, decrease depends finished goods in warehouses. Decrease in receivables includes measures to improve the liquidity and solvency. The current strategy of domestic enterprises should focus on a healthy competitive position across the market, ensuring maximum profitability and economic stability. Keywords: Financial strategy, forecasting, planning, financial resources, the balance sheet